Dynamical suppression of Coulomb interaction and sub-fs jitter correction in electron pulse compression - Yingpeng Qi; Yan Yang; Haitao Sun; Xuan Wang; Jianming Cao; Ralph Ernstorfer; Zhenrong Sun (New Journal of Physics, 2020)
Achieving a few-femtosecond (fs) temporal resolution in electron diffraction and electron microscopy is essential for directly tracking the electronic processes and the fastest atomic motions in molecule and condensed matter systems. The intrinsic Coulomb interaction among electrons broadens the pulse duration and restricts the temporal resolution. To tackle this issue, the electron pulse compression by the time-varying electric fields at optical, THz and RF wavelengths has been demonstrated recently. However, the Coulomb interaction still exists in the compression process and the impact of the Coulomb interaction to the compression remains largely unaccounted for. In this work, we quantify the impact of the Coulomb interaction and present three intrinsic characters of Coulomb interaction in the compression process: the Coulomb interaction is dynamically suppressed as the compression field strength rises; the electron pulse with arbitrary kinetic energy (eV to MeV) suffers the same amount of Coulomb interaction, i.e. the Coulomb interaction is independent on the kinetic energy in compression; the dynamical suppression of Coulomb interaction within a single pulse gives rise to a dispersion of the temporal focus and impedes the further compression to attosecond. Potential applications based on the revealed characters of the Coulomb interaction in the compression process are discussed. Based on the dynamical evolution of the Coulomb interaction, three stages are identified to describe the compression process, which is beyond the ballistic compression model. Additionally, a robust and noninvasive jitter correction approach matching well with the compression regime is presented and the proof-of-principle experiment demonstrates a sub-fs accuracy.